Physicochemical and Biopharmaceutical Controllability of New Self-Assembled Fatty Acid Conjugated Leuprolide for the Enhanced Anticancer Activity - Ngo, Hai V.; Bak, Hye Eun; Nguyen, Hy D.; Lee, Kye Wan; Park, Chulhun; Lee, Beom Jin (International Journal of Nanomedicine, 2023)
Background: Leuprolide (LEU), a synthetic nonapeptide analog of naturally occurring gonadotropin-releasing hormone (GnRH), could exert a direct inhibitory activity on the proliferation of prostate cancer cells. However, the short half-life in blood and the biopharmaceutical problem of LEU limit this anticancer activity. Purpose: To improve its druggability for improving anticancer activity, the amine-group targeted LEU was conjugated with different chain lengths of saturated fatty acids (FAs). Methods: LEU–fatty acid conjugates (LFCs) were synthesized by exploiting N-hydroxysuccinimidyl (NHS) conjugation chemistry. The physicochemical properties and the self-assembled behaviors of the conjugates were extensively investigated. The in vitro anticancer activity of three LFCs was extensively studied in both 2D monolayer and 3D spheroid culture models of a prostate cancer cell line, PC3. Results: Three LFCs could be readily self-assembled into nanoparticles (LFNs) with a small size of around 100 nm, positive charges, and exhibited greater permeability rates compared to the same concentration of LEU, excluding LSN. The chain length of FA in conjugate was positively related to the selectivity index between cancer cells and non-cancerous cell lines. All LFCs showed a superior direct antiproliferative effect on cancer cells in the following order: LSC (98.9%) > LPC (86.7%) > LLC (75.0%) > LEU (8.9%) after repeat daily of the same dose strength of LEU for 4 days. In addition, the 3D spheroid model study indicates that all LFCs with a one-time treatment performed a long-acting inhibitory effect on tumor growth as compared to LEU after 7 days. Conclusion: The conjugation of LEU with different chain lengths of FAs could provide a novel strategy to improve peptide stability and exert an additional superior direct inhibitory effect for the treatment of several hormone-responsive tumor systems using therapeutic peptides.
Keywords: Biological Products; Cell Line, Tumor; Fatty Acids; Gonadotropin-Releasing Hormone; Humans; Leuprolide; Male; Prostatic Neoplasms; enhanced permeability; fattigation; fatty acid chain length; improved anticancer activity; leuprolide; LEU–fatty acid conjugate; self-assembled nanoparticles